Golden Connection Between Stem Cells and Orthopedic Services - Rhatomy,MD, Sholahuddin; Santoso, Asep; Phatama, Krisna Yuarno; Budhiparama, Nicolaas C. (The Hip and Knee Journal, 2022)
Utilization of stem cells in orthopedics has increased dramatically. Consequently, stem cells were discovered to have many roles. Some researchers have used them for regenerative medicine, while some have discovered them as a natural source of immune modulators. Currently, there are several research teams studying the translational potential of stem cells, while clinicians have begun treating patients with orthopedic problems (1).Over the past fifteen years, orthopedic surgeons have prioritized Mesenchymal Stem Cell (MCSs) treatment. Several animal experiments have had favorable results, and there is rising concern over their use in human trials. In these clinical studies, stem cell operations were intended to promote fracture healing and cure nonunion, regenerate articular cartilage in degenerated joints, repair ligament or tendon injuries, and replace degenerative spinal disks (1,2).In past research, stem cells have been used for bone tissue regeneration. Bone tissue engineering presents an alternative treatment that may produce a micromilieu with osteogenic, osteoinductive, and osteoconductive properties. In recent studies, researchers have devised methods for combining MSCs with three-dimensional biodegradable polymeric scaffolds. In addition, Udehiya et al. found that the use of hydroxyapatite scaffolds in conjunction with Bone Marrow-MSCs (BM-MSC) accelerates and enhances the healing of bone segmental defects in a rabbit model compared to the use of hydroxyapatite scaffolds alone. Muwan Chen and colleagues discovered that human BM-MSC combined with hyaluronic acid and b-Tri calcium phosphate-coated polymeric scaffold stimulated osteogenic differentiation, cellular proliferation, and reorganization of the cellular matrix in vitro (1–3).Since 2010, stem cells have undergone a paradigm shift where previously stem cells can differentiate and heal injured organs. This stem cell misunderstanding has led some practitioners in the United States and around the world to advertise the availability of stem cell treatments, e.g., MSC can heal blindness, make paralyzed people walk, and makes old tissue young again. In further studies, it was found that at the site of disease, MSCs rarely or never differentiated into tissue at that location, but they do secrete bioactive factors such as growth factors and their therapeutic effects can be analyzed as a site-specific clinical outcome parameter (2–4).